Pengaruh Total Asset Turnover, Gross Profit Margin Dan Debt To Equity Ratio Terhadap Pertumbuhan Laba Pada PT Indofood Sukses Makmur Tbk - Ahmad Yani (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of total asset turnover, Gross Profit margin, debt to equity ratio on profit growth. The population in this study was 31 years and the sample was 10 years. The statistical tool uses SPSS with the classic assumption test, t test and F test. The results in this research partially have total asset turnover, Gross Profit margin, debt to equity ratio have no influence on profit growth while simultaneously they have no effect on profit growth.